Is there a right to remain silent? coercive interrogation and the Fifth Amendment after 9/11 - Dershowitz, Alan M. 1938- (Oxford Univ. Press, 2008)
From the Publisher: The right to remain silent, guaranteed by the famed Fifth Amendment case, Miranda v. Arizona, is perhaps one of the most easily recognized and oft-quoted constitutional rights in American culture. Yet despite its ubiquity, there is widespread misunderstanding about the right and the protections promised under the Fifth Amendment. In Is There a Right to Remain Silent? renowned legal scholar and bestselling author Alan Dershowitz reveals precisely why our Fifth Amendment rights matter and how they are being reshaped, limited, and in some cases revoked in the wake of 9/11. As security concerns have heightened, law enforcement has increasingly turned its attention from punishing to preventing crime
Includes bibliographical references (p. [177]-204) and index
What is the right against self-incrimination? -- The Supreme Court's recent decision -- The limits of textual analysis in constitutional interpretation -- The limits of precedent: which way does the "immunity" analogy cut? -- The limits of historical inquiry -- The privilege over time -- The relevance of constitutional policies underlying the right -- A matter of interpretation -- Conclusion: The case for a vibrant privilege in the preventive state
Keywords: United States / Constitution / 5th Amendment; United States / Supreme Court; United States. -- Supreme Court; United States. -- Constitution -- 5th Amendment; Self-incrimination / United States; Right to counsel / United States; Police questioning / United States; Civil rights / United States; Grondrechten; Verhoor (recht); Zwijgrecht; Civil rights -- United States; Police questioning -- United States; Right to counsel -- United States; Self-incrimination -- United States; Verenigde Staten; USA